Flame-retardant PBT composite plastic and preparation method thereof

By adding modified glass fibers and phytic acid to PBT to form a polymer network, the problems of insufficient toughness and flame retardant performance of traditional PBT materials are solved, and efficient flame retardant performance improvement and material performance optimization are achieved.

CN119875319AActive Publication Date: 2025-04-25QINGDAO ZHONGXIN HUAMEI PLASTICS CO LTD

Patent Information

Application Number
CN202510013529.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-25
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

In actual applications, traditional PBT materials have problems such as poor toughness, brittle fracture, and large shrinkage ratio and warping during injection molding, and are difficult to meet the high flame retardant performance requirements of industries such as electronic and electrical products and automotive interiors.

Method used

By adding modified glass fibers and phytic acid as flame retardants to the PBT, a polymer network with branched structure with phytic acid as the branching center is formed to enhance the toughness and flame retardant properties of the material.

Benefits of technology

It significantly improves the toughness and flame retardant properties of the material, meets high-demand fire safety standards, and maintains or enhances the original excellent characteristics of PBT.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005229154250000131
    Figure BDA0005229154250000131
  • Figure BDA0005229154250000141
    Figure BDA0005229154250000141
Patent Text Reader

Abstract

The invention discloses flame-retardant PBT (polybutylene terephthalate) composite plastic and a preparation method thereof, and belongs to the technical field of PBT materials. The flame-retardant PBT composite plastic disclosed by the invention is prepared from the following raw material components in parts by weight: 49 to 51 parts by mass of PBT, 29 to 31 parts by mass of modified glass fibers, 0.4 to 0.6 part by mass of an antioxidant and 5 to 15 parts by mass of a flame retardant, the modified glass fiber is obtained by firstly pre-modifying glass fiber by adopting a silane coupling agent and then modifying the pre-modified glass fiber by adopting 3-aminopyrrole and 4-aminopyridine; phytic acid is adopted as the flame retardant; the antioxidant is any one or a combination of two of an antioxidant 168 and an antioxidant 1010. According to the invention, the modified glass fiber is added into the PBT, so that the problem of poor dispersibility of the traditional glass fiber in the PBT is solved; meanwhile, the flame retardant is introduced, so that the flame-retardant PBT composite plastic is endowed with excellent flame retardance, the original excellent characteristics of PBT are inherited and enhanced, and the toughness of the material is also remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PBT materials, in particular to a flame retardant PBT composite plastic and a preparation method thereof. Background Art

[0002] Polybutylene terephthalate (PBT) is a thermoplastic engineering plastic with excellent comprehensive performance. Its synthesis process is mature and it is recognized as the fastest growing of the five major engineering plastics. PBT has many excellent properties, including good mechanical properties, fatigue resistance and stability, as well as low creep. These properties give PBT stability in high temperature environments. At the same time, it also has excellent resistance to organic solvents and is not prone to stress cracking. Therefore, since PBT was first introduced, it has been widely used in many fields such as automotive parts, industrial machinery and equipment, household appliances, electronic and electrical, and precision instruments due to its excellent performance.

[0003] However, despite the many advantages mentioned above, PBT also has some limitations in practical applications. In particular, pure PBT material is very sensitive to notch impact, which leads to poor toughness and brittle fracture. In addition, during the injection molding process, PBT products often experience a large shrinkage ratio and obvious warping, which seriously affect the quality and dimensional accuracy of the finished product. In order to overcome these shortcomings, enhancement modification has become a key means to improve the comprehensive performance of PBT.

[0004] At present, technicians add glass fiber for reinforcement to improve its mechanical strength and impact resistance, but the compatibility of glass fiber and PBT is poor, which may lead to uneven dispersion and affect the performance of the final product. Moreover, with the expansion of application areas, especially for demanding industries such as electronic and electrical products and automotive interiors, higher requirements are placed on the flame retardant properties of materials. Traditional PBT materials are difficult to meet the fire safety standards of these industries. Therefore, the development of a composite material that can maintain or enhance the original advantages of PBT, significantly improve its toughness, and have good flame retardancy has become an important direction of current research. Summary of the invention

[0005] The purpose of the present invention is to provide a flame retardant PBT composite plastic and a preparation method thereof, so as to solve the technical problems mentioned in the above background technology.

[0006] The technical solution for achieving the purpose of the present invention is:

[0007] A flame retardant PBT composite plastic comprises raw material components by weight: 49-51 parts by weight of PBT, 29-31 parts by weight of modified glass fiber, 0.4-0.6 parts by weight of antioxidant, and 5-15 parts by weight of flame retardant.

[0008] Furthermore, the modified glass fiber is obtained by first pre-modifying the glass fiber with a silane coupling agent, and then modifying the pre-modified glass fiber with an amino nitrogen-containing heterocycle.

[0009] Furthermore, the silane coupling agent is 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, octaepoxycyclohexylethyl cage-like polysilsesquioxane, or γ-glycidyloxypropylmethyldiethoxysilane.

[0010] Furthermore, the amino nitrogen-containing heterocyclic ring includes 3-aminopyrrole and 4-aminopyridine.

[0011] Furthermore, the antioxidant is any one of antioxidant 168 and antioxidant 1010 or a combination of both.

[0012] Furthermore, the flame retardant is phytic acid.

[0013] The present invention also provides a method for preparing a flame retardant PBT composite plastic, comprising the following preparation steps:

[0014] (1) Weighing and preparing the raw materials according to the weight proportions and raw material components of claim 1, and drying them;

[0015] (2) 29 to 31 parts by weight of modified glass fiber are uniformly dispersed by ultrasonication in 2400 parts by weight of anhydrous ethanol to obtain dispersion E; 10 to 30 parts by weight of a 50 wt% aqueous solution of phytic acid are dissolved in 1200 parts by weight of anhydrous ethanol to obtain solution F; solution E is added to dispersion F and ultrasonic dispersion is continued to be uniformly performed, then the temperature is raised to 69 to 71° C., and the reaction is stirred for 4.5 to 5.5 hours. After the reaction is completed, the solution is cooled to room temperature, filtered, the filter cake is washed with anhydrous ethanol, and dried. The mixture was put into 2400 parts by weight of anhydrous ethanol and ultrasonically dispersed uniformly to obtain a dispersion liquid G; 25 to 26 parts by weight of ferric chloride was dissolved in 79 to 81 parts by weight of anhydrous ethanol to obtain a solution H; the solution H was added dropwise to the dispersion liquid G at a rate of 30 to 40 drops / min and ultrasonically dispersed uniformly, then the temperature was raised to 69 to 71°C, and the reaction was stirred for 1.8 to 2.2 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, the filter cake was washed with distilled water and anhydrous ethanol, and dried to obtain a primary mixture;

[0016] (3) 49-51 parts by weight of PBT and 0.4-0.6 parts by weight of antioxidant are uniformly mixed, and then conveyed to a twin-screw extruder at a rate of 14kg / h-16kg / h for melt dispersion. At the same time, the primary mixture prepared in step (2) is added to the twin-screw extruder from a side feed port at a rate of 6kg / h-7kg / h, and melt-extruded and granulated to obtain a flame-retardant PBT composite plastic.

[0017] Furthermore, the preparation steps of the modified glass fiber are as follows: 1 part by mass of pre-modified glass fiber is ultrasonically dispersed in 31 to 33 parts by mass of anhydrous ethanol for 20 minutes to obtain a dispersion C; then 0.09 to 0.11 parts by mass of 3-aminopyrrole and 0.04 to 0.06 parts by mass of 4-aminopyridine are completely dissolved in 15 to 17 parts by mass of anhydrous ethanol to obtain a solution D; solution D is added dropwise to the dispersion C at a rate of 30 to 40 drops / min and ultrasonic dispersion is continued for 10 minutes, then the temperature is raised to 59 to 61°C, the reaction is carried out for 6.5 to 7.5 hours, and after the reaction is completed, the solution is cooled to room temperature, filtered, the filter cake is washed with distilled water and anhydrous ethanol, and dried to obtain the modified glass fiber.

[0018] Furthermore, the preparation method of the pre-modified glass fiber is as follows: first, 2.4 parts by mass of glass fiber are uniformly ultrasonically dispersed in 39 to 41 parts by mass of toluene to obtain a dispersion A; then 1.1 to 1.3 parts by mass of a silane coupling agent are completely dissolved in 19 to 21 parts by mass of toluene to obtain a solution B; solution B is added dropwise to the dispersion A at a rate of 30 to 40 drops / min and continues to be uniformly ultrasonically dispersed, then the temperature is raised to 89 to 91°C, the reaction is performed for 5.5 to 6.5 hours, and after the reaction is completed, the solution is cooled to room temperature, filtered, the filter cake is washed with anhydrous ethanol, and dried to obtain the pre-modified glass fiber.

[0019] Furthermore, the extrusion temperature of the twin-screw extruder is 230-255° C., and the screw speed is 360 r / min.

[0020] By adopting the above technical solution, the present invention has the following beneficial effects:

[0021] (1) The flame retardant PBT composite plastic of the present invention comprises, by weight, 49 to 51 parts by weight of PBT, 29 to 31 parts by weight of modified glass fiber, 0.4 to 0.6 parts by weight of antioxidant, and 5 to 15 parts by weight of flame retardant. The modified glass fiber is added to PBT to solve the problem of poor dispersion of traditional glass fiber in PBT. At the same time, the flame retardant is introduced to give the flame retardant PBT composite plastic excellent flame retardancy, which not only inherits and enhances the original excellent properties of PBT, but also significantly improves the toughness of the material.

[0022] (2) The modified glass fiber of the present invention is obtained by first pre-modifying the glass fiber with an epoxy silane coupling agent, and then modifying the pre-modified glass fiber with an amino nitrogen-containing heterocycle, wherein the amino nitrogen-containing heterocycle is 3-aminopyrrole or 4-aminopyridine, and the amino groups on the 3-aminopyrrole or 4-aminopyridine react with the epoxy groups on the surface of the pre-modified glass fiber to form hydroxyl groups and secondary amines, and the 3-aminopyrrole or 4-aminopyridine is grafted on the surface of the glass fiber, thereby enhancing the thermal stability of the modified glass fiber.

[0023] (3) Traditional flame retardants are mostly halogens, which release a large amount of smoke and toxic gases when burned, causing harm to the environment and human health. The flame retardant of the present invention uses phytic acid. Phytic acid (PA), also known as inositol hexaphosphate, is a non-toxic, sustainable, and environmentally friendly natural substance extracted from plants. Due to its high phosphorus content and catalytic carbonization, its introduction into flame-retardant PBT composite plastics can give the flame-retardant PBT composite plastics excellent flame retardancy, achieve halogen-free flame retardancy, and be more environmentally friendly and safer.

[0024] (4) In the present invention, phytic acid and modified glass fiber are first preliminarily mixed, and ferric chloride is introduced. The PA structure contains six phosphate structures and multiple phosphate hydroxyl groups. The phosphate hydroxyl groups in the PA structure react with the hydroxyl groups and secondary amines on the modified glass fiber for grafting. With the help of the good compatibility of phytic acid and PBT on the modified glass fiber, the phytic acid is uniformly dispersed in the PBT. At the same time, under the action of ferric chloride, the pyrrole on the modified glass fiber is polymerized to form conductive polypyrrole, forming a polymer network with a branched structure with phytic acid as the branching center, which can effectively disperse stress, so that the flame-retardant PBT composite plastic can absorb more energy when impacted and is not easy to break, thereby giving the flame-retardant PBT composite plastic excellent antistatic properties and increasing the impact resistance of the flame-retardant PBT composite plastic. The iron ions of ferric chloride react with the modified glass fiber to form a conductive polypyrrole. The nitrogen atoms on the pyridine on the fiber coordinate to form a composite flame retardant system with glass fiber modified by silane coupling agent as silicon source, phytic acid (PA) as acid source, and 3-aminopyrrole and 4-aminopyridine as nitrogen source. During combustion, part of the silicon source migrates to the surface of the carbon layer to participate in the formation of a dense carbon layer. 3-aminopyrrole and 4-aminopyridine are partially decomposed into non-flammable gases such as nitrogen and ammonia, which reduce the concentration of flammable gases and play a flame retardant role in the gas phase; PA is mainly decomposed into phosphorus-containing free radicals, which block the combustion chain reaction and play a quenching role. At the same time, it participates in the formation of a phosphorus-containing carbon layer and improves the quality of the carbon layer; iron ions mainly catalyze the degradation process of organic components in the condensed phase, accelerate the carbonization of the matrix to form a dense and continuous carbon layer, and P, N, Si and iron ions play a synergistic flame retardant role, which enhances the excellent flame retardancy of the flame-retardant PBT composite plastic. DETAILED DESCRIPTION

[0025] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.

[0026] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention.

[0027] The following are some examples and comparative examples. The raw material components are as follows:

[0028] The glass fiber used is the glass fiber of model 7E-534 produced by Jushi Group Co., Ltd.

[0029] The remaining raw materials are commercially available.

[0030] Example 1

[0031] A method for preparing a flame retardant PBT composite plastic comprises the following preparation steps:

[0032] (1) 29 parts by weight of modified glass fiber were ultrasonically dispersed in 2400 parts by weight of anhydrous ethanol for 20 minutes to obtain dispersion E; 10 parts by weight of a 50 wt% aqueous solution of phytic acid was dissolved in 1200 parts by weight of anhydrous ethanol to obtain solution F; solution E was added to dispersion F and ultrasonically dispersed for 10 minutes, then heated to 69° C. and stirred for reaction for 4.5 hours. After the reaction was completed, the solution was cooled to room temperature, filtered, the filter cake was washed with anhydrous ethanol, dried, and ultrasonically dispersed in 2400 parts by weight of anhydrous ethanol for 20 minutes to obtain dispersion G; 25 parts by weight of ferric chloride was dissolved in 79 parts by weight of anhydrous ethanol to obtain solution H; solution H was added dropwise to dispersion G at 30 drops / min and ultrasonically dispersed for 10 minutes, then heated to 69° C. and stirred for reaction for 1.8 hours. After the reaction was completed, the solution was cooled to room temperature, filtered, the filter cake was washed with distilled water and anhydrous ethanol, and dried to obtain a primary mixture;

[0033] (2) 494 parts by weight of PBT and 0.44 parts by weight of antioxidant were uniformly mixed, and then conveyed to a twin-screw extruder at a rate of 14 kg / h for melt dispersion. At the same time, the primary mixture obtained in step (2) was added to the twin-screw extruder from a side feed port at a rate of 6 kg / h for melt extrusion and granulation to obtain a flame-retardant PBT composite plastic; wherein the extrusion temperature of the twin-screw extruder was 230° C. and the screw speed was 360 r / min.

[0034] The preparation steps of the modified glass fiber are as follows: first, 2.4 parts by mass of glass fiber are ultrasonically dispersed in 39 parts by mass of toluene for 20 minutes to obtain a dispersion A; then, 1.1 parts by mass of 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane is completely dissolved in 19 parts by mass of toluene to obtain a solution B; the solution B is added dropwise to the dispersion A at a rate of 30 drops / min, and ultrasonic dispersion is continued for 10 minutes, then the temperature is raised to 89°C, and the reaction is carried out for 5.5 hours. After the reaction is completed, the solution is cooled to room temperature, filtered, the filter cake is washed with anhydrous ethanol, and dried to obtain a pre- Modified glass fiber; 1 part by mass of pre-modified glass fiber is ultrasonically dispersed in 31 parts by mass of anhydrous ethanol for 20 minutes to obtain dispersion C; 0.09 parts by mass of 3-aminopyrrole and 0.04 parts by mass of 4-aminopyridine are completely dissolved in 15 parts by mass of anhydrous ethanol to obtain solution D; solution D is added dropwise to dispersion C at 30 drops / min and ultrasonic dispersion is continued for 10 minutes, then the temperature is raised to 59°C, the reaction is carried out for 6.5 hours, and after the reaction is completed, the solution is cooled to room temperature, filtered, the filter cake is washed with distilled water and anhydrous ethanol, and dried to obtain modified glass fiber.

[0035] Example 2

[0036] A method for preparing a flame retardant PBT composite plastic comprises the following preparation steps:

[0037] (1) 30 parts by weight of modified glass fiber were ultrasonically dispersed in 2400 parts by weight of anhydrous ethanol for 20 minutes to obtain dispersion E; 20 parts by weight of a 50 wt% phytic acid aqueous solution were dissolved in 1200 parts by weight of anhydrous ethanol to obtain solution F; solution E was added to dispersion F and ultrasonically dispersed for 10 minutes, then heated to 70°C and stirred for reaction for 5 hours. After the reaction was completed, the solution was cooled to room temperature, filtered, the filter cake was washed with anhydrous ethanol, dried, and ultrasonically dispersed in 2400 parts by weight of anhydrous ethanol for 20 minutes to obtain dispersion G; 25.5 parts by weight of ferric chloride were dissolved in 80 parts by weight of anhydrous ethanol to obtain solution H; solution H was added dropwise to dispersion G at 35 drops / min and ultrasonically dispersed for 10 minutes, then heated to 70°C and stirred for reaction for 2 hours. After the reaction was completed, the solution was cooled to room temperature, filtered, the filter cake was washed with distilled water and anhydrous ethanol, and dried to obtain a primary mixture;

[0038] (2) 50 parts by weight of PBT and 0.5 parts by weight of antioxidant are uniformly mixed, and then conveyed to a twin-screw extruder at a rate of 15 kg / h for melt dispersion. At the same time, the primary mixture obtained in step (1) is added to the twin-screw extruder from a side feed port at a rate of 7 kg / h, and melt-extruded and granulated to obtain a flame-retardant PBT composite plastic; wherein the extrusion temperature of the twin-screw extruder is 245° C. and the screw speed is 360 r / min.

[0039] The preparation steps of the modified glass fiber are as follows: first, 2.4 parts by mass of glass fiber are ultrasonically dispersed in 40 parts by mass of toluene for 20 minutes to obtain a dispersion A; then, 1.2 parts by mass of γ-glycidyl ether oxypropyl methyl diethoxy silane is completely dissolved in 20 parts by mass of toluene to obtain a solution B; the solution B is added dropwise to the dispersion A at 35 drops / min and ultrasonic dispersion is continued for 10 minutes, then the temperature is raised to 90°C, the reaction is carried out for 6 hours, and after the reaction is completed, the solution is cooled to room temperature, filtered, the filter cake is washed with anhydrous ethanol, and dried to obtain a pre-modified Glass fiber; 1 part by mass of pre-modified glass fiber is ultrasonically dispersed in 32 parts by mass of anhydrous ethanol for 20 minutes to obtain dispersion C; then 0.1 parts by mass of 3-aminopyrrole and 0.05 parts by mass of 4-aminopyridine are completely dissolved in 16 parts by mass of anhydrous ethanol to obtain solution D; solution D is added dropwise to dispersion C at 35 drops / min and ultrasonic dispersion is continued for 10 minutes, then the temperature is raised to 60°C and the reaction is carried out for 7 hours. After the reaction is completed, the solution is cooled to room temperature, filtered, the filter cake is washed with distilled water and anhydrous ethanol, and dried to obtain modified glass fiber.

[0040] Example 3

[0041] A method for preparing a flame retardant PBT composite plastic comprises the following preparation steps:

[0042] (1) 31 parts by weight of modified glass fiber were ultrasonically dispersed in 2400 parts by weight of anhydrous ethanol for 20 minutes to obtain dispersion E; 30 parts by weight of a 50 wt% phytic acid aqueous solution were dissolved in 1200 parts by weight of anhydrous ethanol to obtain solution F; solution E was added to dispersion F and ultrasonically dispersed for 10 minutes, then heated to 71°C and stirred for reaction for 5.5 hours. After the reaction was completed, the solution was cooled to room temperature, filtered, the filter cake was washed with anhydrous ethanol, dried, and ultrasonically dispersed in 2400 parts by weight of anhydrous ethanol for 20 minutes to obtain dispersion G; 26 parts by weight of ferric chloride were dissolved in 81 parts by weight of anhydrous ethanol to obtain solution H; solution H was added dropwise to dispersion G at 40 drops / min and ultrasonically dispersed for 10 minutes, then heated to 71°C and stirred for reaction for 2.2 hours. After the reaction was completed, the solution was cooled to room temperature, filtered, the filter cake was washed with distilled water and anhydrous ethanol, and dried to obtain a primary mixture;

[0043] (2) 51 parts by weight of PBT and 0.6 parts by weight of antioxidant were uniformly mixed, and then conveyed to a twin-screw extruder at a rate of 16 kg / h for melt dispersion. At the same time, the primary mixture obtained in step (1) was added to the twin-screw extruder from a side feed port at a rate of 7 kg / h, and melt-extruded and granulated to obtain a flame-retardant PBT composite plastic; wherein the extrusion temperature of the twin-screw extruder was 255° C. and the screw speed was 360 r / min.

[0044] The preparation steps of the modified glass fiber are as follows: first, 2.4 parts by mass of glass fiber are ultrasonically dispersed in 41 parts by mass of toluene for 20 minutes to obtain a dispersion A; then, 1.3 parts by mass of octaepoxycyclohexylethyl cage-shaped polysilsesquioxane is completely dissolved in 21 parts by mass of toluene to obtain a solution B; the solution B is added dropwise to the dispersion A at a rate of 40 drops / min and ultrasonic dispersion is continued for 10 minutes, then the temperature is raised to 91° C., the reaction is carried out for 6.5 hours, and after the reaction is completed, the pre-modified glass fiber is cooled to room temperature, filtered, the filter cake is washed with anhydrous ethanol, and dried to obtain a pre-modified glass fiber. Fiber; 1 part by mass of pre-modified glass fiber was ultrasonically dispersed in 33 parts by mass of anhydrous ethanol for 20 minutes to obtain dispersion C; 0.11 parts by mass of 3-aminopyrrole and 0.06 parts by mass of 4-aminopyridine were completely dissolved in 17 parts by mass of anhydrous ethanol to obtain solution D; solution D was added dropwise into dispersion C at a rate of 40 drops / min and ultrasonic dispersion was continued for 10 minutes, then the temperature was raised to 61°C, the reaction was carried out for 7.5 hours, and after the reaction was completed, the solution was cooled to room temperature, filtered, the filter cake was washed with distilled water and anhydrous ethanol, and dried to obtain modified glass fiber.

[0045] Comparative Example 1

[0046] The difference between Comparative Example 1 and Example 2 is that the modified glass fiber is obtained by modifying the glass fiber only with γ-glycidyloxypropylmethyldiethoxysilane; the remaining steps and components are the same as those in Example 2.

[0047] Comparative Example 2

[0048] The only difference between Comparative Example 2 and Example 2 is that the modified glass fiber is first pre-modified with γ-glycidyloxypropylmethyldiethoxysilane, and then the pre-modified glass fiber is modified with 3-aminopyrrole; the remaining steps and components are the same as Example 2.

[0049] Comparative Example 3

[0050] The only difference between Comparative Example 3 and Example 2 is that the modified glass fiber is first pre-modified with γ-glycidyloxypropylmethyldiethoxysilane, and then the pre-modified glass fiber is modified with 4-aminopyridine; the remaining steps and components are the same as Example 2.

[0051] Comparative Example 4

[0052] The only difference between Comparative Example 4 and Example 2 is that the flame-retardant PBT composite plastic includes, by weight, 50 parts by weight of PBT, 30 parts by weight of glass fiber, 0.5 parts by weight of antioxidant, and 10 parts by weight of flame retardant; the remaining steps and components are the same as those in Example 2.

[0053] Comparative Example 5

[0054] A method for preparing a flame retardant PBT composite plastic comprises the following preparation steps:

[0055] (1) 30 parts by weight of modified glass fiber were ultrasonically dispersed in 2400 parts by weight of anhydrous ethanol for 20 minutes to obtain dispersion E; 20 parts by weight of a 50 wt% aqueous solution of phytic acid were dissolved in 1200 parts by weight of anhydrous ethanol to obtain solution F; solution E was added to dispersion F and ultrasonic dispersion was continued for 10 minutes, then the temperature was raised to 70° C. and stirred for reaction for 5 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, the filter cake was washed with anhydrous ethanol, and dried to obtain a primary mixture;

[0056] (2) 50 parts by weight of PBT and 0.5 parts by weight of antioxidant are uniformly mixed, and then conveyed to a twin-screw extruder at a rate of 15 kg / h for melt dispersion. At the same time, the primary mixture obtained in step (1) is added to the twin-screw extruder from a side feed port at a rate of 7 kg / h, and melt-extruded and granulated to obtain a flame-retardant PBT composite plastic; wherein the extrusion temperature of the twin-screw extruder is 245° C. and the screw speed is 360 r / min.

[0057] The preparation steps of the modified glass fiber are as follows: first, 2.4 parts by mass of glass fiber are ultrasonically dispersed in 40 parts by mass of toluene for 20 minutes to obtain a dispersion A; then, 1.2 parts by mass of γ-glycidyl ether oxypropyl methyl diethoxy silane is completely dissolved in 20 parts by mass of toluene to obtain a solution B; the solution B is added dropwise to the dispersion A at 35 drops / min and ultrasonic dispersion is continued for 10 minutes, then the temperature is raised to 90°C, the reaction is carried out for 6 hours, and after the reaction is completed, the solution is cooled to room temperature, filtered, the filter cake is washed with anhydrous ethanol, and dried to obtain a pre-modified Glass fiber; 1 part by mass of pre-modified glass fiber is ultrasonically dispersed in 32 parts by mass of anhydrous ethanol for 20 minutes to obtain dispersion C; then 0.1 parts by mass of 3-aminopyrrole and 0.05 parts by mass of 4-aminopyridine are completely dissolved in 16 parts by mass of anhydrous ethanol to obtain solution D; solution D is added dropwise to dispersion C at 35 drops / min and ultrasonic dispersion is continued for 10 minutes, then the temperature is raised to 60°C and the reaction is carried out for 7 hours. After the reaction is completed, the solution is cooled to room temperature, filtered, the filter cake is washed with distilled water and anhydrous ethanol, and dried to obtain modified glass fiber.

[0058] Comparative Example 6

[0059] A method for preparing a flame retardant PBT composite plastic comprises the following preparation steps:

[0060] 20 parts by mass of a 50wt% phytic acid aqueous solution, 25.5 parts by mass of ferric chloride, 50 parts by mass of PBT and 0.5 parts by mass of an antioxidant are mixed uniformly, and then transported to a twin-screw extruder at a rate of 15kg / h for melt dispersion. At the same time, 30 parts by mass of modified glass fiber are added to the twin-screw extruder from a side feeding port at a rate of 7kg / h, and melt-extruded and granulated to obtain a flame-retardant PBT composite plastic; wherein the extrusion temperature of the twin-screw extruder is 245°C and the screw speed is 360r / min.

[0061] The preparation steps of the modified glass fiber are as follows: first, 2.4 parts by mass of glass fiber are ultrasonically dispersed in 40 parts by mass of toluene for 20 minutes to obtain a dispersion A; then, 1.2 parts by mass of γ-glycidyl ether oxypropyl methyl diethoxy silane is completely dissolved in 20 parts by mass of toluene to obtain a solution B; the solution B is added dropwise to the dispersion A at 35 drops / min and ultrasonic dispersion is continued for 10 minutes, then the temperature is raised to 90°C, the reaction is carried out for 6 hours, and after the reaction is completed, the solution is cooled to room temperature, filtered, the filter cake is washed with anhydrous ethanol, and dried to obtain a pre-modified Glass fiber; 1 part by mass of pre-modified glass fiber is ultrasonically dispersed in 32 parts by mass of anhydrous ethanol for 20 minutes to obtain dispersion C; then 0.1 parts by mass of 3-aminopyrrole and 0.05 parts by mass of 4-aminopyridine are completely dissolved in 16 parts by mass of anhydrous ethanol to obtain solution D; solution D is added dropwise to dispersion C at 35 drops / min and ultrasonic dispersion is continued for 10 minutes, then the temperature is raised to 60°C and the reaction is carried out for 7 hours. After the reaction is completed, the solution is cooled to room temperature, filtered, the filter cake is washed with distilled water and anhydrous ethanol, and dried to obtain modified glass fiber.

[0062] Effect example

[0063] Charpy notched impact strength: The flame-retardant PBT composite plastics prepared in the embodiments and comparative examples were injection molded in an injection molding machine to prepare standard test specimens. The injection molding temperature was 240-255°C, the nozzle temperature was 255°C, the injection pressure was 40% of the rated pressure, the injection speed was 30% of the rated speed, and the injection time was 3s; the holding pressure was 60% of the rated pressure, and the holding time was 3s; the cooling time was 4s; the melting speed was 65% of the rated speed, and the melting pressure was 50% of the rated pressure. The charpy notched impact strength was tested according to GB / T 1043.1, the test temperature was 23°C, and the pendulum energy was 1J.

[0064] Flame retardancy: The flame retardancy of the flame retardant PBT composite plastics prepared in the examples and comparative examples was tested with reference to the U.S. ANSI / UL-94 standard. The limiting oxygen index test was performed to determine the minimum oxygen concentration required for the flame retardant PBT composite plastics prepared in the examples and comparative examples to maintain flaming combustion in a mixture of N2 and O2. The test was conducted according to GB / T2406.2 standard, and the sample size was 120mm×10mm×4mm.

[0065] Tensile properties: The flame-retardant PBT composite plastics prepared in the embodiments and comparative examples were injection molded in an injection molding machine to prepare standard test specimens. The injection molding temperature was 240-255°C, the nozzle temperature was 255°C, the injection pressure was 40% of the rated pressure, the injection speed was 30% of the rated speed, and the injection time was 3s; the holding pressure was 60% of the rated pressure, and the holding time was 3s; the cooling time was 4s; the melting speed was 65% of the rated speed, and the melting pressure was 50% of the rated pressure. The tensile strength of 5 specimens was tested according to GB / T1040.2, and the final data was averaged.

[0066] Volume resistivity: The flame-retardant PBT composite plastics prepared in the examples and comparative examples were cut into specifications of 100×100×1 mm, and the resistivity was tested according to GB / T31838.2-2019 standard. Each sample was measured at least 5 times, and the average value was taken.

[0067] Table 1 shows the test results of various properties of the flame retardant PBT composite plastics prepared in the examples and comparative examples:

[0068] Table 1

[0069]

[0070]

[0071] It can be seen from Table 1 that the flame retardant PBT composite plastic of the present invention has good flame retardancy, notched impact strength, tensile properties and antistatic properties.

[0072] Among them, compared with Example 2, the modified glass fiber of Comparative Example 1 is not modified with 3-aminopyrrole and 4-aminopyridine, and iron ion ligands and conductive polypyrrole cannot be formed in the flame-retardant PBT composite plastic. Therefore, the flame retardant PBT composite plastic prepared in Example 2 has better flame retardancy and antistatic properties.

[0073] Compared with Example 2, in Comparative Example 2, the modified glass fiber is not modified with 4-aminopyridine, and iron ion ligands cannot be formed in the flame-retardant PBT composite plastic. The flame-retardant PBT composite plastic of Example 2 has better flame retardancy.

[0074] Comparative Example 3 is compared with Example 2. The modified glass fiber is not modified with 3-aminopyrrole, and iron ion ligands and conductive polypyrrole cannot be formed in the flame-retardant PBT composite plastic. The flame-retardant PBT composite plastic of Example 2 has better antistatic properties.

[0075] Compared with Example 2, Comparative Example 4 does not use modified glass fiber; the compatibility of glass fiber and PBT base material is poor, resulting in a large amount of glass fiber agglomeration, and the mechanical properties of the flame retardant PBT composite plastic are reduced. 3-aminopyrrole, 4-aminopyridine, and silane coupling agent are not introduced, and iron ion ligands and conductive polypyrrole cannot be formed in the flame retardant PBT composite plastic, and the dispersibility of phytic acid in the PBT base material is also poor. Therefore, the flame retardant PBT composite plastic of Example 2 has better flame retardancy, notched impact strength, tensile properties, and antistatic properties.

[0076] Compared with Example 2, Comparative Examples 5 and 6 do not introduce ferric chloride in Comparative Example 5, and Comparative Example 6 does not preliminarily mix phytic acid, modified glass fiber, and ferric chloride, so that iron ion ligands and conductive polypyrrole cannot be formed in the flame-retardant PBT composite plastic. The flame retardancy, notched impact strength, tensile properties, and antistatic properties of the flame-retardant PBT composite plastic of Example 2 are good. Among them, the notched impact strength and tensile properties of the flame-retardant PBT composite plastic of Comparative Example 6 are poor compared with those of Example 2. This is because the phytic acid aqueous solution, ferric chloride, PBT, and antioxidant are directly mixed. Phytic acid is a strong acid, and direct mixing will cause PBT to decompose, resulting in a decrease in the overall mechanical properties of the flame-retardant PBT composite plastic. In Example 2, phytic acid and modified glass fiber are preliminarily mixed, and ferric chloride is introduced, so that the phosphoric acid hydroxyl group in the phytic acid structure can be reacted and grafted with the hydroxyl group and secondary amine on the modified glass fiber, consuming the acidic groups in the phytic acid, thereby avoiding the introduction of phytic acid to cause PBT decomposition, resulting in a decrease in the overall mechanical properties of the flame-retardant PBT composite plastic.

[0077] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A flame retardant PBT composite plastic, characterized in that: The raw material components include, by weight: 49 to 51 parts by weight of PBT, 29 to 31 parts by weight of modified glass fiber, 0.4 to 0.6 parts by weight of antioxidant, and 5 to 15 parts by weight of flame retardant.

2. The flame retardant PBT composite plastic according to claim 1, characterized in that: The modified glass fiber is obtained by first pre-modifying the glass fiber with a silane coupling agent and then modifying the pre-modified glass fiber with an amino nitrogen-containing heterocycle.

3. The flame retardant PBT composite plastic according to claim 2, characterized in that: The silane coupling agent adopts 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, octaepoxycyclohexylethyl cage-shaped polysilsesquioxane, and gamma-glycidyl ether oxygen propyl methyldiethoxysilane.

4. The flame retardant PBT composite plastic according to claim 2, characterized in that: The amino nitrogen-containing heterocyclic ring includes 3-aminopyrrole and 4-aminopyridine.

5. The flame retardant PBT composite plastic according to claim 1, characterized in that: The antioxidant may be any one of antioxidant 168 and antioxidant 1010 or a combination of the two.

6. The flame retardant PBT composite plastic according to claim 1, characterized in that: The flame retardant is phytic acid.

7. A method for preparing a flame retardant PBT composite plastic, characterized in that: The method comprises the following preparation steps: (1) Weighing and preparing the raw materials according to the weight proportions and raw material components of claim 1, and drying them; (2) 29 to 31 parts by weight of modified glass fiber are uniformly dispersed by ultrasonication in 2400 parts by weight of anhydrous ethanol to obtain dispersion E; 10 to 30 parts by weight of a 50 wt% aqueous solution of phytic acid are dissolved in 1200 parts by weight of anhydrous ethanol to obtain solution F; solution E is added to dispersion F and ultrasonic dispersion is continued to be uniformly performed, then the temperature is raised to 69 to 71° C., and the reaction is stirred for 4.5 to 5.5 hours. After the reaction is completed, the solution is cooled to room temperature, filtered, the filter cake is washed with anhydrous ethanol, and dried. The mixture was put into 2400 parts by weight of anhydrous ethanol and ultrasonically dispersed uniformly to obtain a dispersion liquid G; 25 to 26 parts by weight of ferric chloride was dissolved in 79 to 81 parts by weight of anhydrous ethanol to obtain a solution H; the solution H was added dropwise to the dispersion liquid G at a rate of 30 to 40 drops / min and ultrasonically dispersed uniformly, then the temperature was raised to 69 to 71°C, and the reaction was stirred for 1.8 to 2.2 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, the filter cake was washed with distilled water and anhydrous ethanol, and dried to obtain a primary mixture; (3) 49-51 parts by weight of PBT and 0.4-0.6 parts by weight of antioxidant are uniformly mixed, and then conveyed to a twin-screw extruder at a rate of 14kg / h-16kg / h for melt dispersion. At the same time, the primary mixture prepared in step (2) is added to the twin-screw extruder from a side feed port at a rate of 6kg / h-7kg / h, and melt-extruded and granulated to obtain a flame-retardant PBT composite plastic.

8. The method for preparing the flame retardant PBT composite plastic according to claim 6, characterized in that: The preparation steps of the modified glass fiber are as follows: 1 part by mass of pre-modified glass fiber is ultrasonically dispersed in 31-33 parts by mass of anhydrous ethanol for 20 minutes to obtain a dispersion C; then 0.09-0.11 parts by mass of 3-aminopyrrole and 0.04-0.06 parts by mass of 4-aminopyridine are completely dissolved in 15-17 parts by mass of anhydrous ethanol to obtain a solution D; the solution D is added dropwise to the dispersion C at a rate of 30-40 drops / min and ultrasonic dispersion is continued for 10 minutes, then the temperature is raised to 59-61°C, the reaction is carried out for 6.5-7.5 hours, and after the reaction is completed, the solution is cooled to room temperature, filtered, the filter cake is washed with distilled water and anhydrous ethanol, and dried to obtain the modified glass fiber.

9. The method for preparing the flame retardant PBT composite plastic according to claim 8, characterized in that: The preparation method of the pre-modified glass fiber is as follows: first, 2.4 parts by mass of glass fiber is uniformly dispersed in 39-41 parts by mass of toluene by ultrasonic dispersion to obtain dispersion A; then, 1.1-1.3 parts by mass of silane coupling agent is completely dissolved in 19-21 parts by mass of toluene to obtain solution B; solution B is added dropwise to dispersion A at a rate of 30-40 drops / min and ultrasonic dispersion is continued to be uniform, then the temperature is raised to 89-91°C, the reaction is performed for 5.5-6.5 hours, and after the reaction is completed, the solution is cooled to room temperature, filtered, the filter cake is washed with anhydrous ethanol, and dried to obtain the pre-modified glass fiber.

10. The method for preparing the flame retardant PBT composite plastic according to claim 6, characterized in that: The extrusion temperature of the twin-screw extruder is 230-255° C., and the screw speed is 360 r / min.

Citation Information

Patent Citations

  • Glass fiber reinforced halogen-free flame-retardant PBT and preparation method thereof

    CN101993583A

  • Halogen-free flame-retardant reinforced PBT (Polybutylene Terephthalate) material with high flame retardance and precipitation resistance and preparation method thereof

    CN114230985A

  • Preparation process of glass fiber composite material reinforced modified PET (Polyethylene Terephthalate) material

    CN118165316A

  • Halogen-free flame-retardant enhanced PBT composition capable of transmitting laser, and preparation and use of halogen-free flame-retardant enhanced PBT composition

    WO2024083096A1

Cited By

  • High-temperature-resistant size-stable nylon material and preparation method thereof

    CN122234601A